The genetic basis and interaction of genes conferring resistance to Puccinia hordei in an ICARDA barley breeding line GID 5779743 - Dinh, Hoan X.; Pourkheirandish, Mohammad; Park, Robert F.; Singh, Davinder (Frontiers in Plant Science, 2022)
Leaf rust of barley causes significant losses in crops of susceptible cultivars. Deploying host resistance is the most cost-effective and eco-sustainable strategy to protect the harvest. However, most known leaf rust resistance genes have been overcome by the pathogen due to the pathogen’s evolution and adaptation. The discovery of novel sources of genetic resistance is vital to keep fighting against pathogen evolution. In this study, we investigated the genetic basis of resistance in barley breeding line GID 5779743 (GID) from ICARDA, found to carry high levels of seedling resistance to prevalent Australian pathotypes of Puccinia hordei. Multipathotype tests, genotyping, and marker-trait associations revealed that the resistance in GID is conferred by two independent genes. The first gene, Rph3, was detected using a linked CAPS marker and QTL analysis. The second gene was detected by QTL analysis and mapped to the same location as that of the Rph5 locus on the telomeric region of chromosome 3HS. The segregating ratio in F2 (conforming to 9 resistant: 7 susceptible genetic ratio; p > 0.8) and F3 (1 resistant: 8 segregating: 7 susceptible; p > 0.19) generations of the GID × Gus population, when challenged with pathotype 5477 P− (virulent on Rph3 and Rph5) suggested the interaction of two genes in a complementary fashion. This study demonstrated that Rph3 interacts with Rph5 or an additional locus closely linked to Rph5 (tentatively designated RphGID) in GID to produce an incompatible response when challenged with a pathotype virulent on Rph3+Rph5.